PENGARUH HUMAN CAPITAL, STRUCTURAL CAPITAL, DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI KANTOR KEMENTERIAN AGAMA KABUPATEN PADANG PARIAMAN - Syaiful Hadi; Evi Susanti Tasri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
This study aims to determine the effect of Human capital, Structural capital and Organizational Commitment to Job Satisfaction of the Office of the Ministry of Religion of Padang Pariaman Regency. (4) Human capital, Structural and organizational commitment have a joint effect on job satisfaction for employees of the Ministry of Religion, Padang Pariaman Regency. The population in this study were all employees of the Ministry of Religion of Padang Pariaman Regency as many as 62 people. This study uses Multiple Linear Regression which aims to determine how much influence the independent variable has on the dependent variable. Human capital, structural capital and organizational commitment together have a significant effect on job satisfaction of the employees of the Ministry of Religion Office of Padang Pariaman Regency.